Digital Transformation Readiness of Hospital Information Management Systems: The Role of Technology and IT Personnel Strategies at Teaching Hospital - Utari, Deasy Farah; Ananta, Rizki; Satria, Riri; Firdausi, Ahmad (Dinasti Research, 2026)
The digital transformation of Hospital Information Systems (HIS) has become an urgent necessity, particularly for teaching hospitals that fulfill the triple mission of healthcare service, education, and research. The gap between technological planning and Information Technology Human Resource (IT HR) readiness is a primary barrier to implementation, even when future business process flows are carefully designed. This study intends to develop an integrated HIS digital transformation roadmap aligned with technological and IT HR strategies for the 2026–2029 period. A qualitative case study approach was used, focusing on the IT division of a teaching hospital in Indonesia. Data were collected through a documentation study of the Hospital’s 2025–2029 Strategic Plan, in-depth interviews with five key informants representing IT division, and observations. Data analysis followed a strategic cascading framework, integrating the Ward and Peppard, the Balanced Scorecard, and Bernard Marr’s Future Skills framework. The findings identify eight primary technology strategy clusters and eight IT HR competency domains encompassing technical, human, and business skills. The Balanced Scorecard analysis produced sixteen measurable strategic objectives. The resulting integrated roadmap is divided into four phases, operating on the principle that IT HR competency development must precede the implementation of new technologies. This research delivers a traceable, strategic cascading model from the hospital’s Strategic Plan to the implementation roadmap, which is replicable for other teaching hospitals in Indonesia facing the challenges of HIS digital transformation